Allgemeine Schreibkunst. Teil I. Aus der nachgelassenen Handschrift „optegnelser til en pasigraphie “ (1823) - Rask, Rasmus Kristian (Glottodidactica, 2005)
The famous Danish philologist R.K. Rask, one of the founders of historical linguistics, has left in a manuscript of 1823 the outline of a minor treatise "Almindelig Skrivekunst" (i.e. "general art of writing/spelling"). It deals with issues of writing systems and develops, as well as discusses, suggestions for a rational Roman-script transliteration of "Oriental" alphabets. The following is an annotated translation by Otto Back (Vienna) of the Danish handwritten original, preceded by the translator's introductory remarks.